How to start from scratch? Vilnius University is launching alumni platform - Biržytė, Giedre (ICAReAlumni Conference Proceedings, 2019)
We took rather unpopular decision and decided to craft an alumni platform ourselves to suit our own specific needs. We are planning to launch it in May. Platform will not only provide opportunity for two way communication, include first time ever donation campaign, but also provide alumni with a virtual alumni service card. Alumni for a long time await for the opening of universities‘ services. For this to happen we had to do a huge homework of digitalizing alumni profiles from 1954 to 2001 for the verification purposes. Will we succeed with effective start? Will we attract thousands of alumni to the platform? Is that a right marketing strategy? Come and hear, come and share. We start from scratch. If you are or have been in a similar situation, it would be lovely to discuss with you.